2018
DOI: 10.3351/ppp.2017.8845235448
|View full text |Cite
|
Sign up to set email alerts
|

Women and homelessness: putting gender back on the agenda

Abstract: 50 years since the first screening of the powerful TV drama 'Cathy Come Home', and 30 years after the first homelessness legislation in the UK, this paper reflects on the continued invisibility of women's homelessness in scholarly and policy debate, It argues that homelessness is inherently gendered, yet rarely recognised as such, and that new conceptualisations of homelessness that take account of gender differentials is urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 14 publications
1
19
0
7
Order By: Relevance
“…[102,103] For instance, previous research has shown that homelessness or unstable housing among women can be harder to detect due to hesitancy in self-identifying as such due to the associated stigma. [104] Furthermore, trauma or severed social ties upon separation from an abusive partner can increase the risk of social isolation and emotional distress. Including equity-related considerations around sex, gender and diversity can increase the reach and impact of interventions; thus, enabling these interventions to better meet the diverse needs of homeless women and their families.…”
Section: Discussionmentioning
confidence: 99%
“…[102,103] For instance, previous research has shown that homelessness or unstable housing among women can be harder to detect due to hesitancy in self-identifying as such due to the associated stigma. [104] Furthermore, trauma or severed social ties upon separation from an abusive partner can increase the risk of social isolation and emotional distress. Including equity-related considerations around sex, gender and diversity can increase the reach and impact of interventions; thus, enabling these interventions to better meet the diverse needs of homeless women and their families.…”
Section: Discussionmentioning
confidence: 99%
“…The women's experiences of homelessness were diverse, but there was evidence supporting the conclusions of some of the more recent work on gender and homelessness Reeve, 2018). Women reported contact with formalised homelessness services but were also often relying on informal support from family, friends and acquaintances when they experienced homelessness.…”
Section: Pathways Through Homelessnessmentioning
confidence: 63%
“…A proper understanding of the specific intersections between gender on homelessness does require further, dedicated research (Bretherton, 2017;Bretherton and Pleace, 2018;Reeve, 2018). This article adds to the evidence that there are some differences in how women can experience homelessness, in terms of how it is caused, experienced and how it may be exited.…”
Section: Discussionmentioning
confidence: 93%
“…Nearly all of the material that the review uncovered around 'gender' norms was concerned with the experiences of women. This is because much research and practice has historically been (even if inadvertently so) concerned with the needs of men and women have remained 'hidden' (Reeve, 2018).…”
Section: The Role Of Gender Norms and Gender Inequalitymentioning
confidence: 99%